Baby Becomings: Towards a Dramaturgy of Sympoietic Worlding - Hovik, Lise; Pérez, Elena (Nordic Theatre Studies, 2020)
The article proposes new concepts of dramaturgical thinking for baby theatre productions. With an arts-based research approach, allowing insider perspectives of the artmaking process to come forth, the authors, who are the director and dramaturge of the performance Baby Becomings by Teater Fot, discuss different concepts of postdramatic dramaturgical aspects in relation to the work. By adapting Donna Haraway’s theories of sympoiesis and science art worldings as a theoretical framework, the article explores how Haraway’s philosophy serves both as artistic inspiration and provides new concepts for dramaturgical reflection. The authors ask how posthumanist and sympoietic perspectives connect to postdramatic dramaturgy and wish to propose a posthumanist dramaturgy of sympoietic worlding in theatre for babies.